Short-term Administration of Alphacalcidol is Associated with More Significant Improvement of Muscular Performance in Women with Vitamin D Deficiency Compared to Native Vitamin D - Capatina, C.; Caragheorgheopol, A.; Berteanu, M.; Poiana, C. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Introduction: Positive relationships between muscle function and vitamin D (VD) status, defined by serum 25-hydroxy VD (25OHD) levels have been reported and muscle strength is generally improved with VD supplementation in deficient individuals. The effects of active VD analogs have been less studied.Aim: We aim to investigate the effect of short-term treatment with native VD (cholecalciferol) or alphacalcidol on the muscular function and physical performance in women with vitamin D deficiency.Material and methods: We analysed 178 women with VD deficiency, defined as serum 25-hydroxyVD-25OHD concentration below 30 ng/ml. We recorded the grip-strength and the results of the chair-rise test (CRT) and timed-up-and-go test (TUG). We randomised the patients to receive cholecalciferol 1 000 IU daily or alphacalcidol 1 μg daily, for 6 months.Results: The mean baseline 25OHD concentration was 14.47±6.57 ng/ml. After treatment the serum 25OHD level rose to 20.85±8.88 ng/ml, significantly higher in cases supplemented with cholecalciferol (22.7±8.32 ng/ml) compared to those treated with alphacalcidol (13.5±7.29 ng/ml, p=0.000). After treatment, significant improvements of TUG and CRT test results (− 6.48 and−5.05% compared to baseline, respectively, p=0.000) and gripstrength (7.85% compared to baseline, p=0.000) occurred. The benefit was more significant in cases treated with alphacalcidol for gripstrength (p=0.001), TUG (p=0.002), CRT (p=0.033). After treatment, the gripstrength increased significantly more in patients with severe baseline VD deficiency.Conclusions: VD status improvement is associated with an increase in muscular performance in women with VD deficiency. Alphacalcidol exerts significantly better effects compared to cholecalciferol, and this can not be explained by a larger increase in serum 25OHD concentration.
Keywords: vitamin D deficiency; muscle performance; cholecalciferol; alphacalcidol